Does the technique of limb lengthening affect physeal growth in patient with achondroplasia? Comparison of the simultaneous and consecutive tibia and femur lengthening with external fixators. Issue 1 (January 2023) - Balci, Halil İbrahim; Anarat, Fikret Berkan; Bayram, Serkan; Eralp, Levent; Şen, Cengiz; Kocaoğlu, Mehmet
Abstract : We aimed to retrospectively investigate and compare patients who underwent bilateral simultaneous and consecutive lengthening surgery of the femur and tibia in terms of the effect on physeal growth. We hypothesize that compared with the sequential lengthening technique, simultaneous lengthening of the bilateral femur and tibia affects physeal growth to a greater extent. Twenty-six patients with achondroplasia who operated in our clinic between 1995 and 2015 for limb lengthening were included in the study. Fourteen patients with bilateral lengthening of the femur and tibia at the same time were named as simultaneous bilateral lengthening (SBL). Twelve patients with bilateral lengthening of the femur and then bilateral tibia lengthening in other sections or vice versa, at a different time was named consecutive bilateral lengthening (CBL). All patients were followed until at least 18 years old. The physeal arrest was measured with predicted final length at the first visit (investigated with the multiplier method), the total amount of lengthening, and final clinical, and radiological length. Mean limb lengthening was 145 mm (48.5%) and 151 mm (46.6%) for simultaneous and consecutive groups respectively. For lower extremity length, the first group reached 527.6 mm while the expected was 447.3 mm. Considering 151 mm lengthening, the mean growth disturbance for the SBL group was 70.7 mm and for the CBL group was 47.5 mm. For total height comparing between two groups, disturbance for height was 80.5 mm and 65.4 mm, respectively. Although there was no statistical difference, simultaneous bilateral femoral and tibial lengthening has more physiological physeal disturbance effects than consecutive lengthening in patients with achondroplasia.